Participatory and Place-Based Socioeconomic Knowledge Generation: An Experience in Community-Based Research Pedagogy - Palka, Jessica (Teaching and Learning Inquiry, 2024)
This article uses fieldnotes along with student and practitioner feedback to recount the challenges, benefits, and broader learnings of engaging master’s students in a participatory research seminar. The students developed research proposals about a real-world socioeconomic challenge with and for local practitioners. Proposals were consistent with the principles and practices of participatory action research (PAR). The planning, implementation, and assessment of this course was informed by feminist scientific philosophies of collaboration, situatedness, partiality, accountability, and a sensitivity to power dynamics. In line with both PAR and SoTL principles, there was an explicit emphasis on partnership, reflexivity, and broad forms of learning in both the classroom and practitioner meetings. The students were challenged by the unfamiliarity of the research approach, the need to navigate a new way of working directly with stakeholders, as well as the responsibility to the community that participatory approaches espouse. Despite the challenges, the students were eager to soak up local knowledges, reflect on their role as researchers, and contribute constructively if they could. Read the corresponding ISSOTL blog post here.